Knowledge Management-Based Applications for Monitoring Student Behavior: A Tool to Improve School-Parent Collaboration - Suhendra; Suhardi, Eka; Sunaryo, Widodo; Fadilah, Ahmad Arif (Mimbar Ilmu, 2024)
School counselors play an important role in monitoring and recording student behavior. Accurate implementation is necessary to document such behavior effectively. This research aims to develop a student behavior recording application called a knowledge management-based behavior recording application. The recorded data is then published and can be accessed by parents (sharing knowledge). The research method used is research and development which consists of the following stages: literature review, needs analysis, product development, and product testing. Validation tests conducted by subject matter experts, IT specialists, and managers showed average scores of 96%, 88.4%, and 94%, respectively, which fall within the “excellent” criteria. These results indicate that the behavior recording application is worthy of further development. The results of teacher evaluations regarding usability, increasing knowledge, and benefits of implementation show that 44% strongly agree, 52% agree, and 4% disagree. Parents' evaluations regarding usability, accuracy of recording, and transparency of access to information showed that 48% strongly agreed, 50% agreed, and 2% disagreed. Findings indicate that the app can document student behavior accurately and is suitable for decision-making purposes by schools and parents.